Analysis of using dietary supplements among recreational athletes in Podgorica, Montenegro - Šoškić Miomir; Đorđević Brižita; Veljić Miloš; Veljić Sandra (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2016)
Introduction and objective. Analysis of using dietary supplements (DS) is an important today as it may indicate the need and the ways of rationalising the use of such products. The aim of this study was to determine the frequency of use of the DS by the recreationists, as well as the role of health professionals in the process. Methods. A descriptive epidemiological investigation included a total of 100 recreationists who voluntarily completed the anonymous survey. The research was conducted in five fitness centres in Podgorica. In order to collect data, we used the original questionnaire. Results. The study involved 100 subjects with an average age of 28 years. Survey results have shown that there are a major percentage (43%) of those respondents who use DS continuously, 38% use it occasionally, and 19% never use the DS. Among all respondents, 29% of respondents said that they currently use 2-3, and even 8% said that they used more than 5 different products at the same time. The three most commonly used supplements are vitamins 18.7%, protein supplements 17.26% and amino acids 11.87%. Most of the respondents stated that they buy DS at the pharmacy 25%, in the fitness centre / gym 21.51% or at local resellers 18.02%. The polling data have shown that respondents generally receive recommendations on the use of the DS from fitness instructors / trainers or friends, and at least from physicians, pharmacists and nutritionists. Conclusion. The study shows that a large number of recreationists use the DS irrationally, without clear indications and recommendations by health professionals. It is necessary to make additional educational efforts not only regarding health care professionals but also regarding those who work in fitness centres to better inform users about the use of the DS.